SUSTAINABLE DEVELOPMENT GOALS DISCLOSURES AND COMPANY VALUES - Elin Erlina Sasanti; Susi Retna Cahyaningtyas; R. Sapto Hendri Boedi Soesatyo (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2020)
The existence of a global governance agenda requires companies all over the world to get involved in implementing Sustainable Development Goals (SDGs). However, previous study showed that corporate involvement in the achievement of SDGs is overall still limited and question on the company motives to disclose SDGs remains unclear. Therefore, the objective of this study is to analyze the association between SDGs disclosures and company values. This study also aimed to analyze the moderating effect of type of industry on the association between SDGs disclosures and company values. Study was conducted on companies listed in IDX, which disclosed SDGs in their Sustainability Reports. The results of this study suggest SDGs disclosures is associated to company value, which confirmed the signaling motives in the involvement of corporate SDGs. The results also showed that different types of industry could weaken the relationship between SDGs disclosure and company values, when associated with high-profile industry companies.